Implementasi Pendekatan CLPBI Untuk Meningkatkan Hasil Belajar Fisika Pada Siswa SMA - Budi Hartati (Jurnal Penelitian Pembelajaran Fisika, 2019)
The learning outcomes of physics subjects of twelfth grade students in SMA Negeri 2 Pekalongan are still relatively low. It is because the students’ learning motivation is still not maximized; there have not been sufficient teaching aids and also the students are less active in the learning process. A classroom action research was conducted by using Cooperative Learning Problem Based Instruction (CLPBI) approach assisted by Melde learning tools. This research was done toward twelfth grade students in learning material of waves to improve their critical thinking skills, learning activities and outcomes. This classroom action research was carried out with several steps: problem identification, theoretical review of the learning tools, theoretical review of the learning outcomes, theoretical review of CLPBI approach, and analysis of the learning outcomes. The subjects researched were twelfth grade students in SMA Negeri 2 Pekalongan which were 32 respondents in total. The research data were obtained from the results of tests and observations using activity observation sheets. Then, the data were analysed by comparing the results of cycle I and II. The results showed that the critical thinking skills, learning outcomes and learning activities of the students in the first cycle was improved after being given the action of CLPBI approach assisted by Melde learning tools in learning material of waves. Keywords: CLPBI, learning outcomes, critical thinking